1977
DOI: 10.1126/science.318761
|View full text |Cite
|
Sign up to set email alerts
|

Tris(2,3-Dibromopropyl) Phosphate: Mutagenicity of a Widely Used Flame Retardant

Abstract: Tris(2,3-dibromopropyl) phosphate, a widely used flame-retardant additive for textiles, is mutagenic to histidine-requiring strains of Salmonella typhimurium. Extracts of fabrics treated with this compound are also capable of inducing mutations in these bacterial strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(49 citation statements)
references
References 11 publications
1
48
0
Order By: Relevance
“…It induced mutations in Salmonella typhimurium strains TA 1535, TA100 and TA 104 in the presence and absence of metabolic activation, with higher mutagenic activity observed in the presence of metabolic activation (Blum and Ames, 1977;Carr and Rosenkranz, 1978;Lynn, et al, 1982;Prival et al, 1977;Salamone and Katz, 1981;as cited by NICNAS, 2005;Vanbeerendonk et al, 1994). TDBPP was negative in strains TA 1537 and TA1538 in the presence and absence of metabolic activation (Carr and Rosenkranz, 1978;Blum and Ames, 1977;Prival et al, 1977, as cited by NICNAS, 2005. In another study, TDBPP has been reported to be mutagenic in S. typhiumurium TA98 and TA100 in the presence, but not in the absence of metabolic activation (Kubo et al, 2002).…”
Section: Hazard Identificationmentioning
confidence: 99%
“…It induced mutations in Salmonella typhimurium strains TA 1535, TA100 and TA 104 in the presence and absence of metabolic activation, with higher mutagenic activity observed in the presence of metabolic activation (Blum and Ames, 1977;Carr and Rosenkranz, 1978;Lynn, et al, 1982;Prival et al, 1977;Salamone and Katz, 1981;as cited by NICNAS, 2005;Vanbeerendonk et al, 1994). TDBPP was negative in strains TA 1537 and TA1538 in the presence and absence of metabolic activation (Carr and Rosenkranz, 1978;Blum and Ames, 1977;Prival et al, 1977, as cited by NICNAS, 2005. In another study, TDBPP has been reported to be mutagenic in S. typhiumurium TA98 and TA100 in the presence, but not in the absence of metabolic activation (Kubo et al, 2002).…”
Section: Hazard Identificationmentioning
confidence: 99%
“…A) by Rosenkranz (1975). Prival et al (1977) reported DBCP to be a direct weak mutagen in Salmonella typhimurium (TA 1535) and Blum & Ames (1977) and others (Biles et al, 1979;Stolzenberg & Hine, 1979) presented data that DBCP was mutagenic with metabolic activation in Salmonella TA 100. Biles et al (1979) showed the influence of contaminants on the mutagenic activity of DBCP.…”
mentioning
confidence: 97%
“…The biological properties of Tris-BP as well as its mutagenicity and carcinogenicity have been previously reported [Blum and Ames, 1977;Prival et al, 1977;NCI Carcinogenesis Technical Report, 19781.…”
Section: Ntro D Uctlo Nmentioning
confidence: 98%
“…Attention has recently been given to Tris-BP metabolites, with the result that a number of presumed and confirmed metabolites and analogs have been tested and shown to be mutagenic [Prival et al, 1977;Carr and Rosenkranz, 1978;Nakamura et al, 1979;Soderlund et al, 1979;Stolzenberg and Hine, 19801. Additionally, a major mutagenic metabolite, 2,3-dibromopropanol, has been identified in the urine of children exposed to Tris-BP-treated sleepwear [Blum et al, 19781. This study was undertaken to determine the mutagenicity of a group of methylated Tris-BP metabolites.…”
Section: Ntro D Uctlo Nmentioning
confidence: 99%